Conservation Choices in the Face of Sea-Level Rise: A Case Study on Marsh Migration from Phippsburg, Maine. (30th August 2017) - Dissanayake, Sahan T. M.; Hennessey, Meagan K.
Abstract : We analyze the benefits of incorporating climate change into land conservation decisions using wetland migration under rising sea-levels as a case study. We use a simple and inexpensive decision method, a knapsack algorithm implemented in Excel, with (1) simulation data to show that ignoring sea-level rise predictions lead to suboptimal outcomes, and (2) an application to land conservation in Phippsburg, Maine to show the real-world applicability. The simulation shows an 11-percent to almost 30-percent gain in increased benefits when accounting for sea-level rise. The results highlight that it is possible to, and important to, incorporate sea-level rise into conservation planning.